Proteomic profiling of serum of women with BI-RADS 1 to 5: identification of potential complementary biomarkers for early detection of breast cancer - Jacqueline, Jaime Jayapalan; Jane, Christina Vellan; Tania Islam; Nur Aishah Mohd Taib; Karuthan Chinna (Penerbit Universiti Kebangsaan Malaysia, 2024)
Mammography remains the gold standard for the screening of breast cancer (BrCa) despite its shortcomings. Cancer antigen 15-3, an FDA-approved biomarker, is most useful as a treatment response and recurrence monitoring tool rather than for early detection of BrCa. Given this, we aimed to screen for potential complementary diagnostic protein biomarkers in the serum of women with BI-RADS 1 to 5. Individual neat sera of women with BI-RADS 1 to 5 (N = 33) were subjected to two-dimensional electrophoresis (2-DE) for the separation of proteins. Comparative analysis of the 2-DE silver-stained gel images was performed using Progenesis SameSpots software. The identification of protein spots of interest was determined following tandem MS/MS analysis and database search using either MASCOT or X! Tandem Vengeance search engines. Data are available via ProteomeXchange with the identifier PXD040427. The Bioinformatics tools of The Database for Annotation, Visualization, and Integrated Discovery were used for the functional annotation of the proteins of altered abundance. A total of 8 non-redundant proteins including albumin, apolipoprotein A-I, apolipoprotein A-II, clusterin, complement C3, immunoglobulin kappa constant, kininogen-1, and leucine-rich alpha-2 glycoprotein were found significantly overexpressed in the sera of women with BI-RADS 4 and/or 5 (p < 0.01, FC ≥ 2). Functional annotation of the significantly differentially expressed proteins showed their possible roles in the development of BrCa. The identified protein signatures are potential biomarkers for use in complement with mammography for improved detection of BrCa at an early stage.